Sprawling cities and transport: preliminary findings from Bristol, UK - Paul Longley; Michael Batty; Nancy Chin (European Regional Science Association (ERSA), 2002)
As part of the Fifth Framework Programme, SCATTER (Sprawling Cities And TransporT : from Evaluation to Recommendations) is examining the mechanisms and impacts of urban sprawl in six case study cities. One of these is Bristol, UK (metropolitan population c. 700,000), where the effects of deregulation, competitive attempts to attract and create new enterprise and greater responsiveness to consumer preferences have all in recent years led to a weakening of the grip of regional and local planners upon urban development. In the country, despite changing government targets for the re-use of 'brownfields' land, this has frequently led to urban sprawl. During the 1960s and 1970s the locus of manufacturing activity shifted to suburban sites, and a growing population was accommodated in suburban developments. During the last 20 years, retailing activity has been allowed to follow these pervious movements, with the result that the UK has one of the highest incidences of out-of-centre retailing in the EU. During the late 1990s these centrifugal tendencies, coupled with a laissez-faire approach to urban planning, led to the development of a large number of peripheral out-of-centre shopping centres, similar in function (if not always in size) to the shopping malls of the USA. This paper will provide a progress report on the Bristol case study, and present some preliminary recommendations to prevent, mitigate or control urban sprawl. Our mandate is to consider, inter alia: evaluation of the impacts of the measures; possible difficulties or barriers to implementation (institutional barriers, low public acceptability, high cost, delay in the impacts, etc.); possible negative side effects; and recommendations concerning the efficient implementation of new public transport services. In addition, we hope to generalise these findings into practical recommendations and guidelines for cities faced with urban sprawl in general, and to devise measures that might inhibit further urban sprawl and the negative effects of existing developments. Finally, we hope to devise an 'urban sprawl monitoring tool' (i.e. a list of relevant indicators), so that local authorities might be empowered to monitor the evolution of sprawl and assess the effects of sprawl upon the environment, and hence devise a practical programme of palliative measures.
Keywords: 330